Diseño de una guía de cuidado y conservación visual para trabajadores que utilizan pantallas de visualización de datos - CONVI (2021)
The purpose of this applied project refers to the design of a visual care and conservation guide for workers who use data visualization screens (CONVI), to respond to the needs arising from continuous and prolonged exposure to the use of data visualization screens (DSP), during long working days. This arises as a result of the health emergency caused by Covid 19, which forced the working population to perform their activities from their homes, as a primary measure to prevent the spread of the virus.